2021
DOI: 10.21203/rs.3.rs-413371/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Meta-Analysis of The Effects of Grazing On Plant Diversity, Biomass and Soil Properties of Alpine Grassland On The Tibetan Plateau

Abstract: Aim As one of the main human disturbance factors in the alpine grassland on the Tibetan Plateau, grazing not only directly affects grassland plant diversity and biomass, but also indirectly changes soil carbon (C) and nitrogen (N) of grassland. Despite of extensive field grazing experiments, the impacts of grazing on grassland diversity, soil C and N remain uncertain due to different grazing management.Methods We conducted a meta-analysis of 70 peer-reviewed publications to evaluate the general response of 11 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 71 publications
(106 reference statements)
0
0
0
Order By: Relevance
“…Numerous studies have substantiated these findings. For instance, in a series of exclosure experiments conducted over 6, 11, and 12 years on the alpine grassland of the Qinghai-Tibet Plateau, Li et al [30] observed that exclosure significantly reduced the Shannon-Wiener diversity index and Margalef richness index of vegetation. Similarly, research conducted in Arizona, southwestern United States, demonstrated that grazing exclusion resulted in a decrease in native species and reduced the overall species richness compared to moderate grazing [31].…”
Section: Effects Of Long-term Exclosure On the Diversity And Biomass ...mentioning
confidence: 99%
“…Numerous studies have substantiated these findings. For instance, in a series of exclosure experiments conducted over 6, 11, and 12 years on the alpine grassland of the Qinghai-Tibet Plateau, Li et al [30] observed that exclosure significantly reduced the Shannon-Wiener diversity index and Margalef richness index of vegetation. Similarly, research conducted in Arizona, southwestern United States, demonstrated that grazing exclusion resulted in a decrease in native species and reduced the overall species richness compared to moderate grazing [31].…”
Section: Effects Of Long-term Exclosure On the Diversity And Biomass ...mentioning
confidence: 99%